2014
DOI: 10.1080/17441692.2014.970659
|View full text |Cite
|
Sign up to set email alerts
|

Exploring loss to follow-up among women living with HIV in Prevention of Mother to Child Transmission programmes in Côte d'Ivoire

Abstract: The expansion of Prevention of Mother to Child Transmission (PMTCT) services globally has been accompanied by significant rates of loss to follow-up (LTFU). This study explored barriers and facilitators to participation in PMTCT programmes for pregnant and post-partum women living with HIV who had been LTFU at public sector antenatal care facilities in the Vallée du Bandama region of Côte d'Ivoire, West Africa. Three types of interviews were conducted at seven health sites: (1) individual or small group interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 16 publications
10
31
2
Order By: Relevance
“…The results of this study demonstrates that multi-factors play a role in mothers choice of continuation with PMTCT services and are similar to studies in Gomba district, Uganda(35), in Cote-d'Ivore (36), in Malawi (37)and in Malawi and Uganda (38). The themes of stigma and discrimination, social determinants and partial access reported in this study are shared across these studies as major barriers to retention in PMTCT program (35,(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study demonstrates that multi-factors play a role in mothers choice of continuation with PMTCT services and are similar to studies in Gomba district, Uganda(35), in Cote-d'Ivore (36), in Malawi (37)and in Malawi and Uganda (38). The themes of stigma and discrimination, social determinants and partial access reported in this study are shared across these studies as major barriers to retention in PMTCT program (35,(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 84%
“…Stigma and discrimination is reported as a major barrier across studies and countries and it was reported as a major issue by the participants including internalized stigma (35,37,38,40,41). Despite, information on HIV be widely available through all media, this study con rmed that stigma and discrimination are still a major issue in HIV in Ethiopia and in other African states stigma (35,37,38,40,41)). Unlike ndings from Schechter et al (40) stigma in Amhara region is not largely internalized but rather from the community and sometimes health care professionals.…”
Section: Discussionmentioning
confidence: 54%
“…These findings are consistent with studies reporting suboptimal uptake and adherence to PMTCT regimens in women who had not disclosed their HIV status (Ebuy, Yebyo, & Alemayehu, 2015; Jasseron et al, 2013; Kinuthia et al, 2011; Spangler, Onono, Bukusi, Cohen, & Turan, 2014) and add to the literature on disclosure and MTCT. Strategies to maintain confidentiality and facilitate disclosure to male partners are needed to maximize PMTCT effectiveness (Kinuthia et al, 2011; Schechter et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Most qualitative research on barriers to PMTCT utilization and reasons for disengagement have drawn from interviews primarily or exclusively with community members including leaders and men (810), providers (812), HIV-positive pregnant women who are engaged in care (916), women whose status is unknown (8, 10), HIV-negative women (10), or a combination of these groups. At least three studies included women who disengaged from care, but they represented a small minority within the broader study sample (9, 11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…At least three studies included women who disengaged from care, but they represented a small minority within the broader study sample (9, 11, 12). Still other studies have relied primarily on interviews with women who disengaged from care, but those women were enrolled in programs (17, 18), broader interventions such as self-help groups (19), breastfeeding studies (15), or clinical trials (14, 20).…”
Section: Introductionmentioning
confidence: 99%